Vulnerability and resilience to pandemic-related stress among U.S. women pregnant at the start of the COVID-19 pandemic. (December 2020) - Preis, Heidi; Mahaffey, Brittain; Heiselman, Cassandra; Lobel, Marci
Abstract: Rationale: Women pregnant during the COVID-19 pandemic are experiencing moderate to high levels of emotional distress, which has previously been shown to be attributable to two types of pandemic-related pregnancy stress: stress associated with feeling unprepared for birth due to the pandemic (Preparedness Stress) and stress related to fears of perinatal COVID-19 infection (Perinatal Infection Stress). Objective . Given the well-documented harms associated with elevated prenatal stress and the critical importance of developing appropriately targeted interventions, we investigated factors predictive of pandemic-related pregnancy stress. Method . Between April 25 and May 15, 2020, 4, 451 pregnant women in the U.S. were recruited via social media to complete an online questionnaire that included sociodemographic, medical, and COVID-19 situational factors, as well as the Pandemic-Related Pregnancy Stress Scale (PREPS). Binary logistic regression was used to calculate odds ratios for high stress. Results . Nearly 30% of participants reported high Preparedness Stress; a similar proportion reported high Perinatal Infection Stress. Abuse history, chronic illness, income loss due to the pandemic, perceived risk of having had COVID-19, alterations to prenatal appointments, high-risk pregnancy, and being a woman of color were associated with greater levels of one or both types of stress. Access to outdoor space, older age, and engagement in healthy behaviors were protective against stress. Conclusions . Practices that may alleviate pandemic-related stress such as minimizing disruptions to prenatal care, ensuring access to outdoor space, and motivating engagement in health behaviors are of vital importance. Particular attention is needed for more vulnerable populations including women of color, women with a history of abuse, and those with high-risk pregnancy. Research focused on the short and longer-term impact of pandemic-related pregnancy stress on maternal mental and physical health, perinatal outcomes, and child development is critical to identify these effects and marshal appropriate resources to reduce them. Highlights: Nearly one-third of pregnant women highly stressed by the COVID-19 pandemic. High pandemic-related pregnancy stress more common in women of color. Changes to medical care are a strong contributor to pregnant women's stress. Having outdoor access is associated with lower pandemic-related pregnancy stress. Pandemic-related stress during pregnancy may increase risk of adverse outcomes.